Fiber material as well as preparation method and application thereof

By mixing the discarded mask with hydrophilic materials and temperature-sensitive materials, fiber materials with shrinkage function are prepared, which solves the problem that concrete structures are prone to cracks under temperature changes and loads, and achieves the effect of improving crack resistance and extending service life.

CN119685952APending Publication Date: 2025-03-25SHENZHEN METRO GROUP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411849266.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Concrete structures are prone to cracks under temperature changes and loads, resulting in a shortened structure service life and an increase in maintenance costs.

Method used

By mixing the discarded mask with hydrophilic material and temperature-sensitive material, and undergoing high temperature melting and impregnation of coolant, fiber material with shrinkage function is prepared. The fibrous material generates prestresses in concrete through a temperature shrinkage induction mechanism, reducing temperature and shrinkage stress.

Benefits of technology

Effectively inhibit concrete cracking, improve crack resistance and later toughness, and extend the service life of concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190765570000091
    Figure BDA0005190765570000091
  • Figure BDA0005190765570000092
    Figure BDA0005190765570000092
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a fiber material and a preparation method and application thereof. The preparation method comprises the following steps: mixing the waste mask without a nose frame strip and ear hooks with a hydrophilic material, melting at a high temperature, and extruding and molding; and immersing the extruded and molded material in a cooling liquid for a period of time, taking out and drying to obtain the product. The cooling liquid is an organic solvent containing a temperature sensing material and a compound containing a silicon-oxygen group. The fiber material is compounded with a hydrophilic material, a temperature sensing material and a compound containing a silicon-oxygen group, the elastic modulus is large, concrete cracking can be effectively inhibited, and the fiber material has extremely important significance for reducing cracking of an underground concrete structure of a civil building.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular relates to a fiber material and a preparation method and application thereof. Background Art

[0002] Concrete cracking is a common problem in civil engineering. Cracking not only affects the safety of structural use and shortens the service life of the project, but also causes huge economic losses to subsequent repairs, reinforcement, and even demolition and reconstruction. Concrete cracking mainly consists of structural cracks, expansion joints, cracks caused by the coupling of deformation and load, and durability cracks. Structural cracks account for 5-10% of these cracks, mainly caused by direct stress from static and dynamic external loads and structural secondary stresses; cracks caused by deformation account for more than 80%, mainly caused by plasticity, autogenous volume, and drying shrinkage caused by humidity changes, as well as thermal shrinkage caused by temperature changes; cracks caused by the coupling of deformation and load account for 5-10%, and cracks caused by durability include cracks caused by alkali-aggregate reaction, freeze-thaw, uneven expansion, and poor stability.

[0003] In the early stages of concrete pouring, heat builds up internally due to the heat released by cement hydration, leading to a rise in temperature. When temperature stress exceeds the concrete's tensile strength, cracks appear, affecting the structure's bearing capacity and durability. Cracking is a common problem in underground diaphragm walls of civil buildings. Due to the high cement content and the large amount of heat accumulated from hydration, the maximum internal temperature can reach 70-85°C. Furthermore, the diaphragm walls are subject to significant constraints from the base plate and rock mass, making the combined effects of temperature and shrinkage stress extremely susceptible to cracking. Furthermore, underground diaphragm walls are thick and have thin concrete structures, leading to rapid surface heat dissipation. The temperature difference between the inside and outside of the concrete causes inconsistent shrinkage between the inside and the outside, generating stress. When this stress exceeds the concrete's current tensile strength, the concrete cracks.

[0004] The disposal of discarded masks is an ongoing problem. Incineration produces large amounts of toxic and harmful gases, masks are difficult to degrade naturally, and landfilling pollutes the soil and the environment. If discarded masks could be processed into fibers that shrink when the temperature inside concrete rises, this could effectively reduce the cracking stress caused by temperature differences between inside and outside, minimize cracking in concrete structures, and extend the service life of the structures.

[0005] Chinese patent CN114315253A discloses a highly crack-resistant mass concrete. Based on a conventional mass concrete mix, temperature-shrinkage fibers are added at a volumetric dosage of 0.5-4% to produce this highly crack-resistant concrete. Chinese patent CN117886531A discloses a method for improving the surface crack resistance of concrete using discarded masks and engineering mesh. Disposable masks, minus the metal nose bridge and cotton earrings, and / or the engineering mesh are crushed into fiber lengths of 30-50 μm and 6-9 mm, respectively. The fibers are then mixed in a ratio of 8:2 and added to the cement mortar base, effectively improving the surface crack resistance of the concrete. Chinese patent CN116607225A discloses a method for producing recycled polypropylene fibers from discarded masks. Discarded masks are disinfected and then subjected to high-temperature and high-pressure treatment to produce the recycled polypropylene fibers. The recycled fibers from discarded masks can be used as a concrete reinforcement, improving the compressive and tensile strengths of concrete when added to it. However, the fibers in the existing technology are relatively soft and easily clump together when added to concrete, disperse unevenly, and have poor bonding properties with concrete. Pores are easily generated around the fibers, becoming channels for external media to enter the concrete, affecting durability. Summary of the Invention

[0006] In response to the defects in the existing technology, the present invention provides a fiber material and its preparation method and application. The fiber material is composited with hydrophilic materials, temperature-sensitive materials and silicon-oxygen group-containing compounds, has a large elastic modulus, can effectively inhibit concrete cracking, and is of great significance for reducing cracking in underground concrete structures of civil buildings.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] A method for preparing a fiber material comprises the following steps:

[0009] The discarded masks with the nose piece and ear hooks removed are mixed with hydrophilic materials, melted at high temperature and then extruded into shape;

[0010] The extruded material is immersed in a cooling liquid for a period of time, taken out and dried to obtain the product; the cooling liquid is an organic solvent containing a temperature-sensitive material and a compound containing a silicon oxygen group.

[0011] The material of the mask is generally made of polypropylene material and gauze (or non-woven fabric). In the preparation method provided by the present invention, during the high-temperature melting process, the gauze (or non-woven fabric) will be converted into carbon doped in the polypropylene material, thereby increasing the hardness of the polypropylene fiber and effectively reducing the possibility of polypropylene fiber agglomeration or entanglement during concrete mixing. At the same time, the coolant used in the present invention contains a temperature-sensitive material and a compound containing a silicon oxygen group, which can be compounded to the fiber surface. The high temperature generated during cement hydration can cause the highly oriented molecular chains of the temperature shrinkage-induced fibers to de-orient, thereby causing shrinkage. At the same time, since the groups on the fiber surface have a strong bonding force with the cement, the shrinkage of the fibers produces prestress on the cement. This temperature shrinkage-induced fiber greatly improves the crack resistance and later toughness of the concrete. It can improve the crack resistance of concrete and extend the service life of concrete structures.

[0012] Preferably, the discarded masks are first subjected to ultraviolet irradiation treatment before removing the nose piece and ear hooks. The wavelength of the ultraviolet irradiation is 200nm-275nm, the time is 1-1.5 hours, the ambient humidity is controlled at 40%-60%, and the ambient temperature is controlled at 20℃-40℃.

[0013] Preferably, the mass ratio of the discarded mask without the nose piece and ear hook to the hydrophilic material is 95-98:5-2.

[0014] Preferably, the hydrophilic material is maleic anhydride-grafted polypropylene and / or maleic anhydride-grafted polyethylene. Maleic anhydride-grafted polypropylene and maleic anhydride-grafted polyethylene contain carboxylic acid and ketone groups, resulting in strong hydrophilicity. They can interact with surrounding water molecules through hydrogen bonds and van der Waals forces, thereby absorbing moisture, reducing the presence of pores around the fibers caused by hydrophobicity, improving the adhesion between the fibers and concrete, and simultaneously reducing the ingress of external media into the concrete through the pores around the fibers, thereby improving the concrete's resistance to external erosion and enhancing its durability.

[0015] Further preferably, the hydrophilic material is a mixture of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene in a mass ratio of 1:0.5-1. The main fiber material of the present invention is polypropylene material, and the temperature-sensitive material is polyethylene material. Studies have found that maleic anhydride grafted polypropylene can better combine with polypropylene material, and maleic anhydride grafted polyethylene can better combine with polyethylene material. Therefore, using a mixture of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene can make the temperature-sensitive modified fiber as a whole have excellent hydrophilicity.

[0016] Preferably, the high temperature melting temperature is controlled at 175-190°C for 4-5 minutes. If the high temperature melting temperature is too high or the melting time is too long, it will cause the polypropylene molecular chain to break and thermally decompose, affecting the fiber properties.

[0017] Preferably, the extrusion molding is specifically as follows: adding the high-temperature melted mixture into a screw extruder to extrude the raw yarn, and then performing secondary stretching of the raw yarn at 80° C.-120° C., with each stretching ratio being 6-8 times.

[0018] Further preferably, the diameter of the original silk is 0.4 mm-0.45 mm, and after being stretched twice, the diameter is 0.18 mm-0.2 mm.

[0019] Preferably, the temperature-sensitive material is at least one of polyethylene, chlorinated polyethylene, chlorosulfonated polyethylene, and cross-linked polyethylene. When the temperature-sensitive material is compounded onto the fibers, during the hydration temperature rise phase of the concrete, the high temperature reduces the interaction between the polyethylene molecular chains, causing highly oriented molecular chains to de-orient, resulting in increased thermal shrinkage. Under conditions of internal and external temperature differences, the fibers shrink, reducing internal expansion, thereby reducing internal surface stress gradients and controlling concrete cracks.

[0020] Preferably, the siloxane-containing compound is tetraethyl orthosilicate. The tetraethyl orthosilicate compound on the fiber surface hydrolyzes upon contact with water to produce a large amount of nano-silicon dioxide, which reacts with cement hydration products to produce calcium silicate hydrate, improving the fiber's bonding properties to concrete. The fiber's bonding strength to cement is over three times that of similar materials, reducing the likelihood of the fiber being pulled out of the concrete.

[0021] More preferably, the purity of the tetraethyl orthosilicate is not less than 99.5%.

[0022] Preferably, in the coolant, based on the volume of the organic solvent, the content of the temperature-sensitive material is 200 g / L-300 g / L, and the content of the silicon-oxygen group-containing compound is 100 g / L-150 g / L.

[0023] Preferably, the immersion time in the cooling liquid is 1 min-1.5 min.

[0024] Preferably, the organic solvent is selected from at least one of xylene and toluene.

[0025] The present invention also provides a fiber material, which is prepared by the above preparation method.

[0026] The present invention also provides application of the fiber material in improving the crack resistance of concrete.

[0027] Preferably, the length of the fiber material is 8 mm to 12 mm.

[0028] The beneficial effects of the present invention are at least:

[0029] 1) The present invention provides a method for preparing a fiber material. During the hydration temperature rise stage of the temperature-sensitive material, the high temperature reduces the interaction between polyethylene molecular chains, causing highly oriented molecular chains to deorient, resulting in increased thermal shrinkage. Under conditions of internal and external temperature differences, the fiber shrinks and reduces internal expansion, thereby reducing the internal surface stress gradient and achieving control of concrete cracks.

[0030] 2) The present invention provides a method for preparing a fiber material. The hydrophilic material is maleic anhydride-grafted polypropylene or maleic anhydride-grafted polyethylene. Due to the presence of carboxylic acid and ketone groups in its molecules, it possesses strong hydrophilicity. This allows it to interact with surrounding water molecules through hydrogen bonds and van der Waals forces, thereby absorbing moisture, reducing the porosity around the fiber caused by hydrophobicity, improving the fiber-concrete bond, and reducing the ingress of external media into the concrete through the pores surrounding the fiber, thereby enhancing the concrete's resistance to external erosion and thus improving its durability.

[0031] 3) The present invention provides a method for preparing a fiber material, wherein the siloxy group material is tetraethyl orthosilicate. The tetraethyl orthosilicate composited on the fiber surface hydrolyzes upon contact with water to produce a large amount of nano-silicon dioxide, which reacts with cement hydration products to produce calcium silicate hydrate, thereby improving the bonding performance between the fiber and concrete. The bonding strength between the fiber and cement is more than three times that of similar materials, reducing the possibility of the fiber being pulled out of the concrete.

[0032] 4) The present invention provides a method for preparing a fiber material. During the high-temperature melting process, the cotton gauze is converted into carbon and doped into polypropylene, thereby increasing the hardness of the polypropylene fiber and effectively reducing the possibility of polypropylene fiber agglomeration or entanglement during concrete mixing. The material has excellent dispersibility and can be directly added to a commercial concrete mixing station for mixing and pumping. DETAILED DESCRIPTION

[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are clearly and completely described below. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions shall be followed.

[0034] In the following examples, the discarded masks were sourced from Quzhou Rongbo Biotechnology Co., Ltd.

[0035] The maleic anhydride grafted polypropylene is sourced from Shanghai Qiaowei Chemical Technology Co., Ltd.

[0036] The maleic anhydride grafted polyethylene is sourced from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0037] The temperature-sensitive material comes from Yangzhou Tianshi New Material Technology Co., Ltd.

[0038] The tetraethyl orthosilicate is sourced from Zhangjiagang Xinya Chemical Co., Ltd.

[0039] Example 1

[0040] A method for preparing fiber for concrete crack resistance comprises the following steps: first, the discarded masks are disinfected with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are removed, a hydrophilic material is mixed, and then the mixture is melted at high temperature (the high temperature melting temperature is controlled at 180° C. and the high temperature melting time is 4 minutes, the same below), and then extruded after melting. The formed fibers are immersed in a coolant for 1 minute, removed and dried to obtain the fiber for concrete, wherein the coolant solvent is xylene, which contains 250 g / L of a temperature-sensitive material and 100 g / L of a siloxy group material, and the fibers are impregnated and compounded onto the fiber surface;

[0041] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 95:5, and the hydrophilic material is maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, which are mixed in a ratio of 1:1;

[0042] The temperature-sensitive material is chlorinated polyethylene;

[0043] The silicon oxygen group material is ethyl orthosilicate;

[0044] The extrusion molding is characterized in that: a molten mask is added to a screw extruder, a raw silk with a diameter of 0.45 mm is melt-extruded, and then the raw silk is subjected to secondary stretching, the stretching temperature is 100° C., and the stretching ratio is 6 times.

[0045] Example 2

[0046] A method for preparing fiber for concrete crack resistance comprises the following steps: first, the discarded masks are sterilized with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are removed, a hydrophilic material is mixed and then melted at high temperature, and then extruded into a mold. The molded fibers are immersed in a coolant for 1 minute, removed and dried to obtain the fiber for concrete. The coolant contains xylene as a solvent, 250 g / L of a temperature-sensitive material and 100 g / L of a siloxane material, which are then impregnated and compounded onto the fiber surface.

[0047] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 98:2, and the hydrophilic material is maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, which are mixed in a ratio of 1:1;

[0048] The temperature-sensitive material is chlorinated polyethylene;

[0049] The silicon oxygen group material is ethyl orthosilicate;

[0050] The extrusion molding is characterized in that: a molten mask is added to a screw extruder, a raw silk with a diameter of 0.45 mm is melt-extruded, and then the raw silk is subjected to secondary stretching, the stretching temperature is 100° C., and the stretching ratio is 6 times.

[0051] Comparative Example 1

[0052] A method for preparing fiber for concrete crack resistance comprises the following steps: first, the discarded masks are sterilized with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are removed, a hydrophilic material is mixed and then melted at high temperature, and then extruded into a mold. The molded fiber is immersed in a coolant for 1 minute, removed and dried to obtain the fiber for concrete. The coolant solvent is xylene, which contains 250g / L of a temperature-sensitive material, and the temperature-sensitive material is impregnated and compounded onto the fiber surface.

[0053] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 95:5, and the hydrophilic material is maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, which are mixed in a ratio of 1:1;

[0054] The temperature-sensitive material is chlorinated polyethylene;

[0055] The extrusion molding is characterized in that: a molten mask is added to a screw extruder, a raw silk with a diameter of 0.45 mm is melt-extruded, and then the raw silk is subjected to secondary stretching, the stretching temperature is 100° C., and the stretching ratio is 6 times.

[0056] Comparative Example 2

[0057] A method for preparing fiber for concrete crack resistance comprises the following steps: first, the discarded masks are sterilized with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are removed, a hydrophilic material is mixed and then melted at high temperature, and then extruded into a mold. The molded fibers are immersed in a coolant for 1 minute, removed and dried to obtain the fibers for concrete. The coolant contains xylene as a solvent and contains 100 g / L of a siloxane material, which is impregnated and compounded onto the fiber surface.

[0058] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 95:5, and the hydrophilic material is maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, which are mixed in a ratio of 1:1;

[0059] The silicon oxygen group material is ethyl orthosilicate;

[0060] The extrusion molding is characterized in that: a molten mask is added to a screw extruder, a raw silk with a diameter of 0.45 mm is melt-extruded, and then the raw silk is subjected to secondary stretching, the stretching temperature is 100° C., and the stretching ratio is 6 times.

[0061] Comparative Example 3

[0062] A method for preparing fiber for concrete crack resistance comprises the following steps: first, the discarded masks are sterilized with ultraviolet light, the full plastic strip of the nose frame and the ear hooks are removed, a hydrophilic material is mixed and then melted at high temperature, and then extruded into a mold. The molded fibers are immersed in a coolant for 1 minute, removed and dried to obtain the fiber for concrete. The coolant contains xylene as a solvent, 250 g / L of a temperature-sensitive material and 100 g / L of a siloxane material, which are then impregnated and compounded onto the fiber surface.

[0063] The mixed hydrophilic material, wherein the mass ratio of the discarded mask to the hydrophilic material is 95:5, and the hydrophilic material is maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, which are mixed in a ratio of 1:1;

[0064] The temperature-sensitive material is chlorinated polyethylene;

[0065] The silicon oxygen group material is ethyl orthosilicate;

[0066] The extrusion molding is characterized in that the molten mask is added into a screw extruder to melt and extrude the raw yarn with a diameter of 0.45 mm.

[0067] Test example

[0068] Test specimens were molded according to the proportions in Table 1 (fiber length was controlled between 8 and 12 mm). After demolding one day, they were immersed in 75°C hot water for 6 hours (special curing). They were then removed and cured for up to 7 days (standard curing temperature: 20°C, humidity greater than 95%). Tensile and flexural properties were tested, and the number of fibers pulled out was counted and compared with specimens cured at 20°C. A 1m long fiber was mounted on a scale and placed in a temperature-matched curing room. The temperature was raised from an initial 40°C to 90°C at a rate of 5°C / hour, and fiber deformation was calculated.

[0069] Table 1 Concrete mix ratio

[0070]

[0071] Table 2 Performance test results of the fibers described in Examples 1 to 2 and Comparative Examples 1 to 3

[0072]

[0073] It can be clearly seen from Table 2 that in Examples 1, 2 and Comparative Examples 1 and 3, the fibers compounded with temperature-sensitive materials undergo a temperature increase process in the early stage of concrete pouring. Due to the shrinkage of the fibers, the internal structure of the concrete becomes denser, which is manifested as an increase in tensile and flexural strength, while in Comparative Example 2, which does not have a composite temperature-sensitive material, its mechanical properties decrease. In Examples 1, 2 and Comparative Examples 1 and 3, the fibers compounded with temperature-sensitive materials shrink as the temperature rises, and the maximum shrinkage rate can reach 1.1%. It can be seen from Comparative Example 3 that due to the lack of secondary stretching, its shrinkage rate is much smaller than that of Examples 1, 2 and Comparative Example 1, which are subjected to secondary stretching. It can be seen from Examples 1 and 2 that the increase in the proportion of hydrophilic material is conducive to the bonding of the fiber to the concrete, which is manifested as a low proportion of fiber pullout in Example 1. It can be seen from Example 1 and Comparative Example 1 that the fiber surface is compounded with siloxane group material, which can improve its bonding performance with concrete, while the fiber pullout rate in Comparative Example 1, which is not compounded with siloxane group material, is high.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A method for preparing a fiber material, characterized in that: The following steps are involved: The discarded masks without nose bars and ear hooks are mixed with hydrophilic materials, and then extruded into shapes after being melted at high temperature; The extruded material is immersed in a cooling liquid for a period of time, taken out and dried to obtain the product; the cooling liquid is an organic solvent containing a temperature-sensitive material and a compound containing a silicon-oxygen group.

2. The preparation method according to claim 1, characterized in that: Before removing the nose piece and the ear hooks from the discarded mask, the discarded mask is first subjected to ultraviolet irradiation treatment, the wavelength of the ultraviolet irradiation is 200nm-275nm, the time is 1-1.5 hours, the ambient humidity is controlled at 40%-60%, and the ambient temperature is controlled at 20℃-40℃.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the discarded mask without the nose frame strip and the ear hook to the hydrophilic material is 95-98:5-2.

4. The preparation method according to claim 1 or 2, characterized in that: The hydrophilic material is maleic anhydride grafted polypropylene and / or maleic anhydride grafted polyethylene.

5. The preparation method according to claim 1 or 2, characterized in that: The high temperature melting temperature is controlled at 175° C.-190° C., and the high temperature melting time is 4-5 minutes.

6. The preparation method according to claim 1 or 2, characterized in that: The extrusion molding is specifically as follows: adding the high-temperature melted mixture into a screw extruder to extrude the raw silk, and then performing secondary stretching of the raw silk at 80° C.-120° C., with each stretching multiple being 6-8 times.

7. The preparation method according to claim 1 or 2, characterized in that: The temperature-sensitive material is at least one of polyethylene, chlorinated polyethylene, chlorosulfonated polyethylene, and cross-linked polyethylene; And / or, the compound containing silicon oxygen groups is tetraethyl orthosilicate.

8. The preparation method according to claim 1 or 2, characterized in that: In the cooling liquid, based on the volume of the organic solvent, the content of the temperature-sensitive material is 200 g / L-300 g / L, and the content of the silicon-oxygen group-containing compound is 100 g / L-150 g / L.

9. A fiber material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the fiber material according to claim 9 in improving the crack resistance of concrete.

Citation Information

Patent Citations

  • High-crack-resistance mass concrete

    CN114315253A

  • Method for preparing regenerated polypropylene fibers from waste masks

    CN116607225A

  • Method for improving crack resistance of concrete surface by using waste masks and engineering dense meshes

    CN117886531A